Mechanical and chemical analyses across dental porcelain fused to CP titanium or Ti6Al4V - Souza, Julio C. M.; Henriques, Bruno; Ariza, Edith; Martinelli, Antonio E.; Nascimento, Rubens M.; Silva, Filipe S.; Rocha, Luís Augusto Sousa Marques da [UNESP]; Celis, Jean-Pierre (Elsevier B.V., 2014)
The aim of this study was to evaluate the evolution of mechanical properties and chemical variation across veneering dental porcelain fused to different titanium-based substrates. Test samples were synthesized by fusing dental feldspar-based porcelain onto commercially pure titanium grade II or Ti6Al4V alloy. Samples were cross-sectioned at angles of 10 and 90 degrees to the interface plane. Afterwards, nanoindentation tests and Scanning Electron Microscopy (SEM) imaging coupled to an Energy Dispersive Spectroscopy (EDS) system were carried out across interfaces extending from the metal towards the porcelain area. Elemental diffusion profiles across the porcelain-to-metal interfaces were also obtained by EDS analysis. The mismatch in mechanical properties found in porcelain-to-Ti6Al4V interfaces was lower than that of porcelain-to-CP titanium. Cracking was noticed at low-thickness veneering dental porcelain regions after the nanoindentation tests of samples cross-sectioned at low angles to the interface plane. A wide reaction zone between titanium and porcelain as well as higher incidence of defects was noticed at the porcelain-to-CP titanium interfaces. This study confirmed Ti6Al4V as an improved alternative to CF-titanium as it showed to establish a better interface with the veneering dental porcelain considering the slight chemical interaction and the lower mechanical properties mismatch. The elastic modulus of porcelain-to-Ti6Al4V samples showed to be less sensitive to porcelain thickness variations. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Titanium; Dental porcelain; Metal-ceramic interface; Mechanical properties; Nanoindentation; Chemical analysis